Intrathecal B cell activation in LGI1-antibody encephalitis - Lehmann-Horn, K; Irani, S; Wang, S; Palanichamy, A; Jahn, S; Greenfield, AL; Dandekar, R; Lepennetier, G; Michael, S; Gelfand, JM; Geschewind, MD; Wilson, MR; et al. (Lippincott, Williams and Wilkins, 2020)
Objective: To study intrathecal B-cell activity in leucine-rich, glioma-inactivated 1 (LGI1) antibody encephalitis. In patients with LGI1 antibodies, the lack of CSF lymphocytosis or oligoclonal bands and serum-predominant LGI1 antibodies suggests a peripherally initiated immune response. However, it is unknown whether B cells within the CNS contribute to the ongoing pathogenesis of LGI1 antibody encephalitis.